The Influence of Company Characteristics on Key Audit Matters (KAM) - Putra, Rhahmat Joni Pribody; Dwita, Sany (Universitas Negeri Padang, 2024)
Purpose– This study examines the influence of company characteristics on the disclosure of key audit matters (KAM). Regulations related to KAM will only begin to be implemented in Indonesia in 2022. Disclosure of key audit matters allows users of financial reports to better understand the matters that are considered most important in the audit of financial statements.Design/methodology/approach–The sample for this study consists of 103 financial company listed on the Indonesia Stock Exchange that were chosen by purposive sampling. Spearman's rho analysis is the analysis method used.Findings– The results show that company complexity positively relationship on key audit matters. By contrast, company size, profitability and leverage did not affect the key audit matters of finance sector company listed on the Indonesia Stock Exchange in 2022.Originality/value – Research on key audit matters is still relatively new to be conducted in Indonesia because the implementation of key audit matters regulations will take effect starting for financial reports in 2022. This study uses samples from financial sector companies, because the financial sector is a sector that complies with new regulations.Research limitations/implications–The limitation of this study is that the data generated in this study are not normally distributed so that it cannot use parametric tests, but uses non-parametric tests whose results are not as strong as parametric tests. This research has the implication of providing a reference to find out how the characteristics of companies being audited can affect the number of KAM presented in audit reports in Indonesia. This has effects for the need that corporations disclose their financial performance in a more open manner. In order to disclose material issues in the audit, the auditor is also more meticulous while reviewing the financial statements